Evaluación de las políticas locales de empleo para las mujeres de Engativá en tiempos del Covid-19 (2022)
The pandemic was a challenge for society and for governments, especially when it must be faced at the beginning of a new District and local administration. The mayor of Engativá was designed and implemented the Local Development Plan based on the purposes described in the Bogotá District Development Plan 2020-2024, seeking to meet the needs of the community. The article developed below is the result of contrasting the figures provided in the accountability for the years 2020 and 2021 of the town of Engativá, with the description of the measures implemented for the economic reactivation of the town and its contribution to Bogotá. having the work of deceitful women; In addition the risks that the Local Mayor's Office may have in the development of policies, and the number of beneficiaries in relation to the implemented programs were expressed.